HUBUNGAN HIGIENE DAN SANITASI MAKANAN DENGAN KONTAMINASI BAKTERI ESCHERICHIA COLI DALAM MAKANAN DI WARUNG MAKAN SEKITAR TERMINAL BOROBUDUR, MAGELANG - Rizqi Putri Kurniasih; Nurjazuli Nurjazuli; Yusniar Hanani D. (Jurnal Kesehatan Masyarakat (Undip), 2015)
Food is a basic necessary forhuman life. Foodmay willbe the cause ofthe disruption inour bodyso thatwe become illthrough contaminationof Escherichiacoli infoods. Escherichia coli bacteriacontaminationinfoodmay wiil be  influencedby thehygiene andsanitaryconditions offood stallsarenotqualified. The purposeof this studywas to determinethe association  betweenhygiene and sanitationwithEscherichia coli bacteriacontaminationon foodat food stallaroundBorobudur Station. This type of researchwasexplanatory researchwithcross sectional approach. The population inthis study were all food stallsaroundBorobudur Station amounted to 31food stalls. The sample wasthe entire study population amounted to 31food vendors and 31 foods.Data analysis of this study wereunivariate analysis withfrequency distribution and bivariat analysistotestthe association,usingchi-square testwith asignificance level ofp-value<0.05. Results oflaboratory testsshowedas much as51,6% of samplespositive containEscherichiacoli bacteria. The results showed thatthere was a relationshipbetween the quality offoodsanitationequipmentwithEscherichia coli bacteriacontaminationon food(pvalue = 0.001). In addition,the results alsoshowed nocorrelationbetween thequality of thesanitarypoint of salewithEscherichia coli bacteriacontamination(pvalue =0,565), there was no correlationbetweenthe qualityof foodsanitationwithEscherichia coli bacteriacontamination(pvalue =1), there was norelationshipof sanitaryquality of food presentation with bacteriaEscherichiacoli contamination (pvalue =0,484), andthere was norelationshipbetweenpersonal hygienepracticestradersin maintainingpersonal hygiene themselfandclothingwithEscherichia coli bacteriacontamination(pvalue =0,372).  Fromthis studyit could be concludedthat there was asignificantassociation betweenthequality offoodsanitationequipmentwithEscherichia coli bacteriacontaminationon food.